1994
DOI: 10.1007/bf00232436
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent excitation of motoneurones from spinal locomotor centres in the cat

Abstract: Lumbar motoneurones were recorded intracellularly during fictive locomotion induced by stimulation of the mesencephalic locomotor region in decerebrate cats. After blocking the action potentials using intracellular QX-314, and by using a discontinuous current clamp, it is shown that the excitatory component of the locomotor drive potentials behaves in a voltage-dependent manner, such that its amplitude increases with depolarisation. As the input to motoneurones during locomotion is comprised of alternating exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 30 publications
6
97
1
Order By: Relevance
“…As motoneurons were depolarized, they reached a threshold where their input was significantly amplified (Brownstone et al, 1994). We did not conclusively determine whether this voltage-dependence was due to activation of PICs, NMDA receptors, or both (Brownstone et al, 1991(Brownstone et al, , 1994. Nevertheless, these experiments demonstrated quite clearly that motoneurons do not simply respond passively to synaptic current during behavior.…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 85%
See 1 more Smart Citation
“…As motoneurons were depolarized, they reached a threshold where their input was significantly amplified (Brownstone et al, 1994). We did not conclusively determine whether this voltage-dependence was due to activation of PICs, NMDA receptors, or both (Brownstone et al, 1991(Brownstone et al, , 1994. Nevertheless, these experiments demonstrated quite clearly that motoneurons do not simply respond passively to synaptic current during behavior.…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 85%
“…This prompted a series of experiments with Hultborn in which we demonstrated that the excitatory synaptic input to motoneurons during fictive locomotion activated voltagedependent channels. As motoneurons were depolarized, they reached a threshold where their input was significantly amplified (Brownstone et al, 1994). We did not conclusively determine whether this voltage-dependence was due to activation of PICs, NMDA receptors, or both (Brownstone et al, 1991(Brownstone et al, , 1994.…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 93%
“…It is unlikely that voltage dependence of the EPSPs (Brownstone et al 1994) is responsible for the AM of the MLRevoked PSPs during locomotion. To study these EPSPs, it was necessary to either study nonspiking motoneurons or to hyperpolarize the motoneurons, which would not only eliminate the firing but also take the membrane out of the range of activation for voltage-gated channels.…”
Section: Relationship Of Mlr-evoked Psps To Locomotion and Ldpsmentioning
confidence: 99%
“…3F and 4F) and not one indicative of a negative slope conductance. It would be predicted that these EPSPs would in fact also show some voltage dependence once the motoneurone is sufficiently depolarized, as input from locomotor centers to motoneurones is indeed voltage dependent (Brownstone et al 1994). At such membrane potentials, the EPSP amplitude would likely increase fairly suddenly rather than linearly.…”
Section: Relationship Of Mlr-evoked Psps To Locomotion and Ldpsmentioning
confidence: 99%
“…However, voltage-activated calcium currents in motoneuron dendrites, which generate "persistent inward currents" (PICs), appear to ensure integration of even distal inputs Li and Bennett, 2003). PICs generate plateau potentials (Hounsgaard and Kiehn, 1989;Lee and Heckman, 1996) and amplify synaptic inputs to motoneurons, both excitatory (Brownstone et al, 1994;Bennett et al, 1998;Lee and Heckman, 2000;Jones and Lee, 2006;Powers et al, 2008) and inhibitory (Hultborn et al, 2003;Kuo et al, 2003;Bui et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%